2017
DOI: 10.1177/0271678x17744124
|View full text |Cite
|
Sign up to set email alerts
|

Up-regulation of Wnt/β-catenin expression is accompanied with vascular repair after traumatic brain injury

Abstract: Recent data suggest that repairing the cerebral vasculature after traumatic brain injury (TBI) may help to improve functional recovery. The Wnt/β-catenin signaling pathway promotes blood vessel formation during vascular development, but its role in vascular repair after TBI remains elusive. In this study, we examined how the cerebral vasculature responds to TBI and the role of Wnt/β-catenin signaling in vascular repair. We induced a moderate controlled cortical impact in adult mice and performed vessel paintin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
47
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(54 citation statements)
references
References 57 publications
(92 reference statements)
6
47
0
Order By: Relevance
“…Tan and colleagues reported increased angiogenesis around the hematoma at 7-14 days after ICH likely via a vascular endothelial growth factor (VEGF) mechanisms (Tang et al, 2007) and confirmed in subsequent reports (Zhou et al, 2012). This vascular repair timeline is very similar to what we have reported in traumatic brain injury, albeit via a Wnt/β-catenin mechanism (Salehi et al, 2018a). In stroke, Gleevec protected the BBB, as well as "normalized" vessels within the brain early (1 h) post-injury (Su et al, 2008).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Tan and colleagues reported increased angiogenesis around the hematoma at 7-14 days after ICH likely via a vascular endothelial growth factor (VEGF) mechanisms (Tang et al, 2007) and confirmed in subsequent reports (Zhou et al, 2012). This vascular repair timeline is very similar to what we have reported in traumatic brain injury, albeit via a Wnt/β-catenin mechanism (Salehi et al, 2018a). In stroke, Gleevec protected the BBB, as well as "normalized" vessels within the brain early (1 h) post-injury (Su et al, 2008).…”
Section: Discussionsupporting
confidence: 83%
“…However, adverse vascular events have been reported in patients treated with Gleevec or other related tyrosine kinase inhibitors (Pasvolsky et al, 2015). It is intriguing to speculate that the early lack of effect on vascular morphology seen in our study could be related to downstream effects of Gleevec on BCR-ABL on Wnt/β-catenin cascades (Cilloni and Saglio, 2012) which we have previously reported is involved in late vascular remodeling following traumatic brain injury (Salehi et al, 2018a).…”
Section: Discussionmentioning
confidence: 57%
“…Most of these studies emphasized on the role of β-catenin, the main effector of the canonical Wnt pathway. Indeed, it has been shown that β-catenin expression was increased in the peri-lesional microvasculature of mice at 1 and 7 days post-TBI, whereas it was reduced in injury site 7 days post-TBI (Salehi et al, 2018). A similar expression pattern was reported in a transgenic mouse line reporter for the canonical Wnt pathway activity, TCF:LEF1:H2B-GFP mice (Salehi et al, 2018).…”
Section: Implication In Tbi Pathobiologymentioning
confidence: 57%
“…Indeed, it has been shown that β-catenin expression was increased in the peri-lesional microvasculature of mice at 1 and 7 days post-TBI, whereas it was reduced in injury site 7 days post-TBI (Salehi et al, 2018). A similar expression pattern was reported in a transgenic mouse line reporter for the canonical Wnt pathway activity, TCF:LEF1:H2B-GFP mice (Salehi et al, 2018). Indeed, β-catenin expression increased 24 h after TBI, and was associated to an enhanced angiogenesis within the peri-lesional zone (Salehi et al, 2018).…”
Section: Implication In Tbi Pathobiologymentioning
confidence: 99%
“…Neuronal differentiation is induced by overexpression of β -catenin or the pharmacological inhibition of GSK3 β (the phosphorylating enzyme of β -catenin) [ 89 , 90 ]. This pathway also promotes blood vessel formation during vascular development, as well as the vascular repair process after TBI [ 91 ]. In addition, wogonin (Mol 160) from Achyranthis Bidentatae Radix (the Chen herb) specifically targeted fibronectin (FN1), Bcl-2-binding component 3 (BBC3), and Protein Kinase C delta type (PRKCD).…”
Section: Discussionmentioning
confidence: 99%